Taxonomy of the Cryptopygus complex. IV. Cyclomorphosis in three species of Appendisotoma and description of a new species from Kazakhstan (Collembola, Isotomidae) - Potapov, Mikhail; Babenko, Anatoly; Bu, Yun; Bayartogtokh, Badamdorj; Gulgenova, Ayuna; Luan, Yun-Xia (Zootaxa, 2024)
Appendisotoma bisetosa Martynova, 1970, A. stebayevae (Grinbergs, 1962) and A. sibirica Stebayeva, 1985 are redescribed based on the material from Palaearctic region. Seasonal cyclomorphosis of the three species is distinguished. The winter form is armed with apical lobe on dens, chitinized furca and larger ocelli. Tenaculum, tenent hairs, and pigmentation can also be affected by cyclomorphosis. Dimorphism of species of Appendisotoma resembles that of several species of Proisotoma s. str. Appendisotoma monomorpha sp. nov. is described from Kazakhstan, taxonomic remarks are given to A. absoloni Rusek, 1966 and A. abiskoensis (Agrell, 1939).